HUMAN CAPITAL INVEST AND OUTCOMES (STUDI PADA TRANSFER PEMBELIAN CRISTIANO RONALDO OLEH MANAJEMEN JUVENTUS FC) - Bambang Septiawan (Universitas Islam Balitar, 2018)
This research focuses on investigating the consideration of Juventus FC management for recruiting Cristiano Ronaldo related to human capital invest and outcomes context. Most of theory used in this research is about human capital invest and result or outcomes by Burud and Tumolo. It is descriptive research because it seeks to understand fenomena. The scope of this research is about financial and the subjects skills that deliver advantages for Juventus FC management. The result of this result shows that Juventus FC management consideration for investing the player are his skills, achievements, and market value. Then the outcomes are increasing Juventus stock, tickets and t-shirt sold out, attracting sponsors, and prize of the competition followed.